PENGARUH TINGKAT KEAHLIAN DAN EFEKTIVITAS SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA USAHA KECIL, DAN MENENGAH (UKM) DI KOTA LANGSA DAN PEMANFAATAN TEKNOLOGI SEBAGAI VARIABEL INTERVENING - Karina Chairunnisa; Dewi Rosa Indah; Nasrul Kahfi Lubis (Jurnal Mahasiswa Akuntansi Samudra, 2022)
The purpose of this study was to determine the effect of Expertise Level, and Effectiveness of Accounting Information Systems (AIS) on the Performance of Small and Medium Enterprises (SMEs) in Langsa City through the Utilization of Information Technology. The research sample was taken by stratified sampling method. The number of samples used in the study were 96 respondents. Data analysis used path analysis with 2 equations, namely: I = 10,430 + 0,200 X1 + 0,315 X2 and Y = 6,916 + 0,138 X1 + 0,281 X2 + 0,242 I. Path analysis test results equation 1 shows the level of expertise and effectiveness of accounting information systems (SIA) ) has a significant effect on the use of information technology, while equation 2 shows the level of expertise and effectiveness of accounting information systems (AIS) and the use of information technology has a significant effect on the performance of small and medium enterprises (SMEs). The results of the Sobel test of the use of Information Technology can mediate the effect of Expertise Level with a t-count value = 2.32251 and AIS Effectiveness with a t-count value = 2.14403 on the performance of Small and Medium Enterprises. The results of the coefficient of determination test show the contribution of equation 1 to the value of the correlation coefficient (R) of 0.407 and determination (R2) of 0.166 or 16.6% while the remaining 83.4% is influenced by other variables, and equation 2 the value of the correlation coefficient (R) of 0.637 and determination (R2) of 0.405 or 40.5% while the remaining 59.5% is influenced by other variables.